Severe Parametritis after Vaginal Delivery with Delayed Response to Broad Spectrum Antibiotics: A Case Report - Eslamian , Laleh; saleh, Maasoumeh; Nouri, Behnaz (Novelty in Biomedicine, 2021)
Background: Postpartum infections, also known as puerperal fever, are bacterial infections of the female reproductive tract following childbirth or miscarriage. Symptoms usually include a fever greater than 38.0°C (100.4°F), chills, lower abdominal pain, and possibly bad-smelling vaginal discharge. It usually occurs after the first 24 hours and within the first ten days following delivery, but life-threatening infection may occur within hours of delivery. Cases Report: We reported a case of severe parametritis in the first 24 hours of delivery. Cesarean section is a risk factor for postpartum infections, and response to treatment is lower than vaginal delivery. Our case was a severe pelvic infection after vaginal delivery, and its risk factor was prolonged rupture of the membrane. Therefore, rapid diagnosis and treatment are necessary to prevent abscess formation and sepsis. Conclusion: In this case, rapid treatment with broad-spectrum antibiotics prevented abscess formation, sepsis, and hysterectomy.